Keep you close [large type] : a novel - Cleveland, Karen (Random House Large Print, 2019)
"Stephanie Maddox works her dream job policing power and exposing corruption within the FBI. Getting here has taken her nearly two decades of hard work, laser-focus, and personal sacrifices--the most important, she fears, being a close relationship with her teenage son, Zachary. A single parent, Steph's missed a lot of school events, birthdays, and vacations with her boy--but the truth is, she would move heaven and earth for him, including protecting him from an explosive secret in her past. It just never occurred to her that Zacharay would keep secrets of his own. One day while straightening her son's room, Steph is shaken to discover a gun hidden in his closet. A loaded gun. Then comes a knock at her front door--a colleague on the domestic terrorism squared, who utters three devastating words: 'It's about Zachary.' So begins a compulsively readable thriller of deception and betrayal, as Stephanie fights to clear her son's name, only to expose a shadowy conspiracy that threatens to destroy them both--and bring a country to its knees"-- <U+01C2>c Provided by publisher.